Sorption and desorption of metribuzin with soil and sewage biosolids organic matter: interpretations based on mechanistic and kinetic models - Jackson, Cary Burton, author; Doxtader, Kenneth G., advisor (Colorado State University. Libraries, 2000)
Soil sorption and release mechanisms for pesticides are central to predicting their transport, bioavailability, and biodegradation. It was hypothesized that sewage biosolids added to soil would affect pesticide sorption and desorption and that the sorptive characteristics of biosolids would enhance the release of sorbed metribuzin. Two sandy loam soils containing differing amounts of soil organic matter (1% and 3%) and sewage biosolids (37.5 and 125 mg g-1) were used to evaluate sorption characteristics of metribuzin. The herbicide (14C-ring labeled) was added to soil and soil plus biosolids to obtain six concentrations ranging from 0 to 5.0 ug cm-3. Sorption was measured after 24 h. Desorption was studied using the highest equilibrium concentration from sorption isotherms and was measured over 120 h at 24-h intervals. The sorption and desorption data fit the Freundlich model. More metribuzin was sorbed with the soil with greater amounts of organic matter and with increasing amounts of biosolids. Sorption linearity (nf) increased with increases in organic matter. Sorption decreased with the addition of extracted organic carbon from sewage biosolids, and residual biosolids after removal of labile organic carbon. Desorption was described by an initial linear, fast-release process, followed by an exponential, slow-release process. The magnitude of metribuzin release increased with increasing amounts of biosolids. The differences in desorption and sorption isotherms (hysteresis) decreased with increasing amounts of added biosolids. Sorption characteristics and hysteresis for these soils and the biosolids treatments were explained using the Freundlich and glassy/rubbery models. Reaction kinetic models were used to describe the mechanism of desorption. The organic matter of the soil and amended soil was described as having two-compartments. The first compartment exhibited instantaneous and reversible sorptive sites, with a second compartment exhibiting slow-release kinetic sorptive sites. These results support the theory that the sorptive characteristics of organic matter are responsible for not only the sorptive capacity of the soil but also the mechanisms of sorption and rates of release of sorbate.
Keywords: soil sciences; environmental engineering; agricultural chemicals